Menelaah Mahakarya Muhammad Quraish Shihab: Kajian Metodologis dan Penafsirannya dalam Tafsir Al Misbah - Aisyah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2021)
The interpretation of Al-Misbah was presented by Muhammad Quraish Shihab to meet the needs of society and to answer the problems that arise in society. This article will discuss the biography of Muhammad Quraish Shihab, the background and history of Al-Misbah's exegesis, study the methodology of Al-Misbah's interpretation, the characteristics and peculiarities of his interpretation, and also examine in general the advantages and things that are input into this interpretation. With the descriptive analytic method the researcher studies and describes the theme. And this study found that the Quraish Shihab emphasized a lot through his book Al-Misbah, that it is necessary to understand the Qur’an in a contextualy and not merely be fixated on text so the messages contained in it can be used in real life.